Genetic variants in FKBP5 affecting response to antidepressant drug treatment. (July 2008) - Kirchheiner, Julia; Lorch, Rainer; Lebedeva, Elena; Seeringer, Angela; Roots, Ivar; Sasse, Johanna; Brockmööller, Jüürgen
Introduction: Hyperactivity of the hypothalamic––pituitary––adrenal (HPA) axis is a pathogenic mechanism of depression, and genetic polymorphisms in HPA axis genes have been described to influence response to antidepressant drugs. In particular, two polymorphisms in FKBP5, a co-chaperone of the glucocorticoid receptor, were strongly associated with response to therapy. We aimed to analyze whether these findings could be reproduced in a different sample of otherwise comparable inpatients with major depression.Methods: Genotyping for the two variants within the FKBP5 gene was performed using PCR-restriction fragment length polymorphism and Taqman ®® real-time PCR in a cohort of 179 inpatients who were monitored for the first 3 weeks of antidepressant drug treatment. The early response to antidepressant drugs was assessed as percentage of decline in Hamilton depression score after 3 weeks, responders versus nonresponders were distinguished by a 50% decrease.Results: The FKBP5 variants rs3800373 and rs1360780 were highly linked, and carriers of the FKBP5 variants had a trend towards a higher chance to respond (p  =  0.04; odds ratio: 1.8; 95% CI: 0.98––3.3). When analyzing drug-specific subgroups, the effect was seen mainly in the subgroups of patients treated with antidepressant drug combinations or with venlafaxine.Conclusion: In this study, an effect of FKBP5 variants on antidepressant drug response was confirmed in an independent cohort of depressed patients; however, with an odds ratio of 1.8 the effect size was smaller than that described earlier.